Application of the Task Centered System Design (TCSD) Method for UI / UX Design Analysis in E-Learning at SMAN 1 Sidoarjo - Taufani, Muhamad Nizar; Sagirani, Tri; Nurcahyawati, Vivine (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2021)
SMAN 1 Sidoarjo which is one of the favourite schoolsÂ in the district. When implementing online learning, SMAN 1 Sidoarjo has not used an e-learning platform so it uses many existing platforms such as google classrooms, so students and teachers need to open many platforms, and the UI design e-learning on platforms does not motivate students, causing bored. Because the design user interface in e-learning is an important element for creating virtual-based learning so it is necessary to have a design analysis before building e-learning. The TCSD method is used for the design analysis stage, so that the results are in prototype accordance with the process task and the display results are in accordance with the results of the user persona. Usability heuristic is used to test whether the results prototype are running according to the task with a display that is acceptable to the user. The prototype has been compiled and evaluated, using the evaluation heuristic the SR value for each aspect is obtained with an average of 0.822 rounded to 1, so that the result is in the category cosmetic which means there is a problem but no improvement is needed unless there is still time for processing.